Introduction: Modern Japan and Korea seen through various media - Koma, Kyoko (Acta Orientalia Vilnensia, 2011)
Vytautas Magnus UniversityThis issue discusses cultural aspects of modern Japan and Korea seen through various media. Media in this issue is not simple mass media like newspapers, journals, and TV, but media in a much broader meaning. According to Helen Katz, media has two roles: to inform and to entertain. Newspapers inform but also entertain readers. Literature could also be considered a medium to entertain readers. Autobiographic literature or non-fiction literature informs a kind of reality. Fashion could be also considered a medium for a human being to transmit information (occupation, taste, identity) and entertain (for example, the fashionable style of singers permits them to entertain TV spectators). In this issue, we approach some cultural aspects of modern Japan and Korea as seen through several types of media from popular culture, film, fashion and newspapers to cultural media as a tool of public diplomacy. Our topics are as follows....